ROLE OF ANTHROPOGENIC CANOPY GAPS ON NATURAL REGENERATION PATTERN OF MONOSPECIFIC CERIOPS TAGAL IN RAKAWA LAGOON, SRI LANKA - Thilakaratna, W S; Pathirana, P B M; Kumara, M P (MATTER: International Journal of Science and Technology, 2018)
Mangroves are distinctly dominated in tropical and subtropical areas as special kind of trees, palms, shrubs, vines and ferns. Ceriops tagal is one kind of mangrove species which shows monospecific distribution in Rakawa lagoon in Sri Lanka. There are certain factors which influence the natural regeneration pattern of Ceriops tagal. Light intensity is one of the factors which penetrates through canopy gaps and regulates the growth of seed, seedling and sapling and these canopy gaps are resulted mainly due to anthropogenic canopy eradication. However, the studies on the influence of man-made canopy gaps on natural regeneration pattern of mangroves are limited in Sri Lanka. Therefore, current study was carried out in Rakawa Lagoon in July 2014 to estimate the regeneration pattern of Ceriops tagal by the means of mean seedling, sapling densities and live and dead seed densities in open canopy sites with regard to closed canopy sites. Finally, to compare the mean density values of Seedling plus sapling obtained in July 2013 to get the overall knowledge on the effect of canopy gap on regeneration pattern of Ceriops tagal. Consequently mean density of seedling plus sapling were taken as regeneration class 1 and height of seedlings and saplings and the number of live and dead seeds were documented from randomly selected three homogenous plots ,(4m2 x 3) from open canopy sites and three homogenous plots (4m2 x 3) from closed canopy sites. Two –Sample T- test and Paired T-test of “MINITAB 16 software” were used to analyze and compare the data. Mean density of regeneration class 1 in open canopy sites was significantly higher p=0.02 (p<0.05) than closed canopy sites. Hence canopy gaps play major role in enhancing the natural regeneration and increasing the survivability of Ceriops tagal species. Output of this study can be used for mangroves conservation in Sri Lanka.